2010
DOI: 10.1111/j.2041-1626.2010.00018.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of occlusal splint therapy in temporomandibular joint disorder patients using real‐time ultrasonography

Abstract: Ultrasonographic measurements of the masseter muscle in patients with temporomandibular joint disc displacement with reduction can be a useful tool to assess the effectiveness of occlusal splint therapy. Such conservative measures can significantly reduce masticatory muscle tenderness, especially of the temporalis and masseter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Telkar et al found the mean US thickness of the resting masseter muscle to be 8.71 ± 0.44 [7.90–9.40] mm in their study of 47 patients [ 25 ]. In our study, we calculated the resting US thickness of the right masseter muscle as 8.71 ± 1.91 [5.2–17.30] mm, and the left masseter muscle as i8.62 ± 1.69 [4.7–13.30] mm.…”
Section: Discussionmentioning
confidence: 99%
“…Telkar et al found the mean US thickness of the resting masseter muscle to be 8.71 ± 0.44 [7.90–9.40] mm in their study of 47 patients [ 25 ]. In our study, we calculated the resting US thickness of the right masseter muscle as 8.71 ± 1.91 [5.2–17.30] mm, and the left masseter muscle as i8.62 ± 1.69 [4.7–13.30] mm.…”
Section: Discussionmentioning
confidence: 99%
“…The usage of occlusal splints as an early or conservative treatment modality for TMD patients is currently a very common clinical practice [3, 4, 1013]. Of the many types of manufactured splints used, occlusal stabilization splints made of rigid acrylic and manufactured in contact with all mandibular teeth occlusal surface are preferred for these kinds of conservative treatments according to the literature [4, 8, 11, 13, 14]. Aside from a few sources [8, 15, 16], research has not extensively covered the effects of splint thickness.…”
Section: Discussionmentioning
confidence: 99%